Interim design assessment for the Pueblo Chemical Agent Destruction Pilot Plant (National Academies Press, 2005)
The Program Manager for the Assembled Chemical Weapons Alternatives (ACWA) program of the Department of Defense (DOD) requested the National Research Council (NRC) to review and evaluate the designs for pilot plant facilities to destroy the chemical weapons stored at Pueblo Chemical Depot in Colorado and the Blue Grass Army Depot in Kentucky. To accomplish his tasks, the NRC established the Committee to Assess Designs for Pueblo and Blue Grass Chemical Agent Destruction Pilot Plants (referred to as the ACWA Design Committee). This interim report presents the committee's assessment of the design for the Pueblo Chemical Agent Destruction Pilot Plant (PCAPP). It is based on the initial design documentation, test plans, and various test reports and trade studies that were available to the committee. This documentation is cited throughout the report.